Platform Business Models in the South African Banking Environment - Phiri, Soneni (University of the Witwatersrand, Johannesburg, 2023)
Traditional businesses are known to be linear in nature. However, this linear nature has been disrupted as the advent of technology and in particular the Internet has given rise to digitization and eCommerce. Businesses, like man, by nature are evolving. The 21st century has seen the birth of a new and fast- evolving business model, known as the platform business. Various explanations have been forwarded in an effort to define the very nature of the platform business model. This study aims to address the definition of this model within a South African business framework, with a particular emphasis on the banking sector. Data was collected through qualitative research, by means of face-to-face interviews with predetermined questions posed to a select population of business executives from across various industries. The key findings were that within the business environment there is an understanding of the nature of a platform business. However, its definitions are varied and will evolve with its growth and usage. Furthermore, this study addresses the key distinctions between eCommerce and platform businesses, concluding with a bias towards adopting the platform business model within the banking sector
A research proposal submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration in the field of platform businesses. Johannesburg, 2023
Keywords: Digitisation; eCommerce; Platform economy; Platform business model; Network effect.; UCTD; SDG-8: Decent work and economic growth